The review of cooking, drying, and green extraction methods on general nutritional properties of mealworms and locusts - Mohd Zaini, Nurul Solehah; Lim, Elicia Jitming; Ahmad, Nurul Hawa; Gengatharan, Ashwini; Wan-Mohtar, Wan Abd Al Qadr Imad; Abd Rahim, Muhamad Hafiz (Springer, 2023)
The processing of edible insects as an alternative source of nutrition may be a key driver in the development of a sustainable food and feed system. This review will study two industrial types of insects–mealworms and locusts–and summarize evidence related to the impact of processing on their micro- and macronutritional characteristics. The focus will be on their potential use as food for human consumption as opposed to animal feed. Literature has indicated that these two insects have the potential to provide protein and fat qualities comparable to or better than traditional mammalian sources. For example, mealworms–the larval form of the yellow mealworm beetlepossess a higher fat content, while adult locusts are rich in fibers, especially chitin. However, due to the different matrix and nutrient compositions, the processing of mealworms or locusts at a commercial scale needs to be tailored to minimize nutritional loss and maximize cost efficiency. The stages of preprocessing, cooking, drying, and extraction are the most critical control points for nutritional preservation. Thermal cooking applications such as microwave technology have demonstrated promising results, but the generation of heat may contribute to a certain nutritional loss. In an industrial context, drying using freeze dry is the preferred choice due to its uniformity, but it can be costly while increasing lipid peroxidation. During the extraction of nutrients, the use of green emerging technologies such as high hydrostatic pressure, pulsed electric field, and ultrasound may provide an alternative method to enhance nutrient preservation.